THE POSSIBILITY OF APPLYING THE SIX SIGMA TECHNIQUE IN THE ACCOUNTING UNITS AT THE UNIVERSITY OF SAMARRA / AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF ACCOUNTANTS AND AUDITORS - Mustafa Mohammed Hussein (American Journals, 2023)
The research aimed to test the possibility of applying the Six Sigma methodology in the accounting units operating at the University of Samarra and to address the opinions of accountants and auditors in the accounting units, and (35) a questionnaire was distributed, and (29) answers were obtained, and the research relied on the descriptive analysis method in analyzing the opinions Workers in accounting units, and reached the possibility of applying the Six Sigma methodology at the University of Samarra to provide the requirements for its application, and recommended the need to raise awareness of the importance of modern administrative methods, especially the Six Sigma methodology that serves the work of organizations, whether private or public, because of the return it achieves on the level of the overall performance of the organization.
Keywords: Six Sigma, Application requirements, University of Samarra.